Ancient Logos as Influence on Urban Planner Constantinos A. Doxiadis - Loukaki, Argyro (Actual Problems of Theory and History of Art, 2024)
The famous Greek architect and urban planner Konstantinos Doxiadis (1913–1975) was a 20th century spatial scientist with great vision and important contribution to spatial planning on various scales throughout the globe. Indicatively, in the 1960s he was the lead architect of Islamabad, the new capital of Pakistan. Gifted with sharp intelligence and with superb strategic talent, Doxiadis mobilized state-of-the-art technology to design new cities and whole areas, but also to contribute imaginatively to the advancement of knowledge during a period of postwar and postcolonial restructuring and of absolute trust in the positivist promise of technology. As he said, “what human beings need is not utopia (‘no place’) but entopia (‘in place’) a real city which they can build, a place which satisfies the dreamer and is acceptable to the scientist, a place where the projections of the artist and the builder merge.” However, many of Doxiadis’s other proposals did not materialize, due to unfavorable political and economic constraints. Doxiadis was also known as “the father of ekistics”, which concerns the science of human settlements, including regional, city, plus community planning and dwelling design. The concept of ekistics not only encompasses all scales of human habitation, but also explores the archaeological and historical record of both great cities as well as of settlement patterns. Doxiadis never succumbed to blind trust in science and technology, choosing instead to prioritize human values and vision, real as well as transcendental. Towards this stance, he was prepared by his education and constant references, moral, scientific, philosophical and literary, both ancient and contemporary. In this, he followed the lead of his distinguished mentor, architect Dimitris Pikionis, Professor at the School of Architecture in Athens. A look at the exact manner in which the ancient thought, seen as a major intellectual substratum, influenced Doxiadis’s oeuvre, is the subject of the present analysis. Recently, a fresh round of disagreement broke out in regard to the Acropolis, as a new concrete pathway across much of the site was deemed necessary to facilitate disabled visitors. This addition has been controversial, though the pathways are reversible, cushioned, not directly attached to the surface of the Sacred Rock, and approved by UNESCO. Critics argue that the Rock as a natural monument is devalued. Following the analysis here, a further point may be that the ensuing strong, two-dimensional linearity, which, starting from the Propylaea, frames the Periclean monuments, strengthens a visual manner that evokes Doxiadis’s criticized proposal. But, as we suggested, Doxiadis duly distanced himself from it in later stages of his career, because it contravenes the ancient visual principles and spatial feeling.
Keywords: C. A. Doxiadis; architecture and urban planning; ancient logos as creative legacy; ancient vs modern visual perception; visual and spatial arrangement of ancient precincts; divergent interpretations of the Athenian Acropolis; ekistics; ecumenopolis; Islamabad; Doxiadis and global postcolonial development